INTEGRATED DAYLIGHT HARVESTING AND OCCUPANCY DETECTION USING DIGITAL IMAGING (International Journal of Engineering and Computer Science, 2017)
A case study of a catastrophic failure of a web marine crankshaft and a failure Analysis under bending and torsion applied to crankshafts are presented. A microscopy (eye seen) observation showed that the crack initiation started on the fillet of the crankpin by rotary bending and the propagation was a combination of cycle bending and steady torsion. The crack front profile approximately adopts a semi-elliptical shape with some istortion due to torsion and this study is supported by a previous research work already published by the authors. The number of cycles from crack initiation to final failure of his crankshaft was achieved by recording of the main engine operation on board, taking into account the beach marks left on the fatigue crack surface. The cycles calculated by the linear fracture mechanics approaches showed that the propagation was fast which means that the level of bending stress was relatively high when compared with total cycles of an engine in service. Microstructure defects or inclusion were not observed which can conclude that the failure was probably originated by an external cause and not due to an intrinsic latent defect. Possible effects of added torsional vibrations which induce stresses are also discussed. Some causes are analyzed and reported here but the origin of the fatigue fracture was not clearly determined